Odpowiedź :
Odpowiedź:
Możesz pobrać photomat i tam masz całe rozwiązanie i wyjaśnienie c:
Odpowiedź:
[tex][(\frac{2}{3})^{2}+\frac{4}{3}-(\frac{5}{3})^2] :(\frac{15}{7}*\frac{2}{3})=[\frac{4}{9} +\frac{4}{3} -\frac{25}{9}] :(\frac{10}{7})=-1*\frac{7}{10}=-\frac{7}{10}=-0,7[/tex]
[tex][\frac{5}{3}+\frac{7}{3}*\frac{6}{14}+\frac{5}{2}*\frac{1}{2}]:(\frac{4}{7}*\frac{14}{3}+\frac{7}{3})=[\frac{5}{3}+\frac{5}{3}*1+\frac{5}{4}]:(\frac{8}{3}+\frac{7}{3})=\frac{55}{12}*\frac{3}{15} =\frac{11}{12}[/tex]